Prosedur Pengadaan Barang Dan Jasa Di PT Alfitra Rayavespindo - Umi Zunaidah; Johan Lucas Away; Andi Nurhasanah; Irgi Voller Away (E-BISMARK : Jurnal Ekonomi, Bisnis Dan Marketing, 2021)
The problem discussed is about the Procedure for the Procurement of Goods and Services carried out by the Administrative Section at PT Alfitra Raya Vespindo. The purpose of this study was to determine the process of the procurement of goods and services carried out by the Administrative Section at PT Alfitra Raya Vespindo. The data collection method used is the method of observation, interviews, and literature study. The analysis tool uses the opinion expressed by Christopher & Schonner (2007) in their book entitled "Incrementalism: Eroding the Impediments to a Global Public Procurement Market." Which was quoted by Badzlina Daroyani Novitaningrum as a comparison. Based on the observations that the author got, the existing procedures are in accordance with what Badzalina said. It's just that there is a slight difference in stages. It is hoped that there will be correct and good management procedures in the general section, so that incoming letters are more organized and easy to find if one day they are needed again, providing motivation so that management runs well so that it becomes a satisfactory service.